Three Views on the Problem of A Priori: I. Kant, D. von Hildebrand and M. Scheler - Stepukonis, Aivaras (Problemos, 1999)
The Kantian concept of a priori manifests a twofold meaning: first, that there is a kind of knowledge that is independent of experience; second, that such knowledge is independent of experience through a kind of relatedness to that experience. In short, a priori means both ‘being prior’ and ‘being prior to’. Kant’s a priori encompasses the whole man and is not limited to his intellective faculty. Above all it is an anthropological category, whereas epistemology is but one of its specifications. The term a priori designates a structural dimensions of the being of man which pre-exists al that can ever be given to man and whose application is a necessary subjective condition for anything to be giveable to man at all. Hildebrand claims that each a priori proposition as such possesses three universal features: (1) strict necessity, (2) incomparable intelligibility, and (3) absolute certainty. But what does it mean to call something necessary, intelligible, certain, and• a priori? Von Hildebrand leaves this question unanswered. His a priori in no way supplements, what he calls, propositional necessity, intelligibility and certainty and hence seems to be redundant. Hildebrand uses a priori in yet another sense, namely, in the sense of ‘independent of blunt observation’, but, he does not take the pain of explaining the meaning of the latter phrase. Objective a priori for Scheler means the ontic antecedence of the ideal to the real. As soon as the essences are apprehended by some mind there arises a case of subjective a priori. When somebody apprehends an essence he is affected by that essence and his mind builds up a functional-categorial apparatus whereby it conceptualizes the world. As a result, a thing though or liked becomes a manner of thinking or liking. Scheler names this process 'the functionalization of essences', whole outcome is the subjective a priori structure of the mind. The Schelerian treatment of a priori seems to be the most balanced of the three considered. It takes in Kant's subjective a priori as 'a mental function' and complements it with an objective a priori represented by some ideal essence.